Self‐Folding 3D Silk Biomaterial Rolls to Facilitate Axon and Bone Regeneration. Issue 18 (31st August 2020) - Huang, Yimin; Fitzpatrick, Vincent; Zheng, Nan; Cheng, Ran; Huang, Heyu; Ghezzi, Chiara; Kaplan, David L.; Yang, Chen
Abstract: Biomaterial scaffold designs are needed for self‐organizing features related to tissue formation while also simplifying the fabrication processes involved. Toward this goal, silk protein‐based self‐folding scaffolds to support 3D cell culture, while providing directional guidance and promotion of cell growth and differentiation, are reported. A simple and robust one‐step self‐folding approach is developed using bilayers consisting of a hydrogel and silk film in aqueous solution. The 3D silk rolls, with patterns transferred from the initially prepared 2D films, guide the directional outgrowth of neurites and also promote the osteogenic differentiation of human mesenchymal stem cells (hMSCs). The osteogenic outcomes are further supported by enhanced biomechanical performance. By utilizing this self‐folding method, cocultures of neurons and hMSCs are achieved by patterning cells on silk films and then converting these materials into a 3D format with rolling, mimicking aspects of the structure of osteons and providing physiologically relevant structures to promote bone regeneration. These results demonstrate the utility of self‐folded silk rolls as efficient scaffold systems for tissue regeneration, while exploiting relatively simple 2D designs programmed to form more complex 3D structures. Abstract : Biomaterial scaffold designs are needed to offer self‐organizing features related to tissue formation while also simplifying the fabrication processes involved. Toward this goal, functional silk protein‐based self‐folding scaffolds are reported to support cell culture in 3D, while providing directional guidance and promotion of cell growth and differentiation.